Strontium isotope and element constraints on the paleoenvironment of the latest Ediacaran in the Sichuan Basin, southeastern Tibetan Plateau - Zhang, Xiaojun; Zhou, Gang; Zhang, Pengyuan; He, Yuan; Wei, Zhifu; Wang, Gen; Zhang, Ting; He, Wei; Ma, He; Zhu, Chenxi; Wei, Jingyi; Ma, Xueyun; et al. (Frontiers in Earth Science, 2022)
The Ediacaran–Cambrian period witnessed the episodic extinctions, oxygenation of seawaters, Cambrian explosions and tectonic events. However, compared with the various high-resolution geochemical records of the early-middle Ediacaran and Cambrian, the available geochemical record of the latest Ediacaran (551–542 Ma) is scarce (especially the strontium isotope and elements), which leads to the ambiguous interpretation of the paleoenvironment of the latest Ediacaran. Therefore, we conducted measurements of strontium isotopes and elemental contents of a continuous series of carbonate samples from the Dengying Formation of Well PT1, located in the Sichuan Basin, Southeastern Tibetan Plateau, in order to constrain the paleoenvironment of the latest Ediacaran. Strict sample screening was used to ensure that the isotopes and elements were not affected by diagenesis. Our analyses show that the environment and geochemical records of the seawater were controlled by the tectonic activities, especially the Gondwana assembly. The global strontium isotope correlation indicates the Sichuan Basin was a restricted basin (high 87Sr/86Sr values, ~0.7090) which can be attributed to the existence of a submarine high. Under the background of oxic environment, there were two episodes of anoxic expansion. During the initial stage, the stable terrigenous detrital input and oxic environment provided the prerequisite for the emergence of aerobic organisms in the restricted platform. Then, the decreasing sea level and intense tectonic activities improved the terrigenous detrital input with higher 87Sr/86Sr values (~0.7095), which stimulated the emergence of aerobic organisms, furthering resulting in the first episode of anoxic environment. Lastly, a global transgressive resulted in a high sea level, and thus the Sichuan Basin changed to an open platform. The exchange with extensive oceans led to the increased paleoproductivity, which consumed oxygen and nutrients, further resulting in the second episode of anoxic environment. Thus, the restriction degree, eustatic variations and the terrigenous detrital input affected the biological evolution and redox conditions.